2013
DOI: 10.5194/bg-10-1799-2013
|View full text |Cite
|
Sign up to set email alerts
|

Detecting an external influence on recent changes in oceanic oxygen using an optimal fingerprinting method

Abstract: Ocean deoxygenation has been observed in all major ocean basins over the past 50 yr. Although this signal is largely consistent with oxygen changes expected from anthropogenic climate change, the contribution of external forcing to recent deoxygenation trends relative to natural internal variability is yet to be established. Here we conduct a formal optimal fingerprinting analysis to investigate if external forcing has had a detectable influence on observed dissolved oxygen concentration ([O2]) chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 69 publications
6
58
1
Order By: Relevance
“…Yet there is no such model-data agreement over most of the tropical oceans. Observed time series suggest a vertical expansion of the lowoxygen zones in the eastern tropical Atlantic and the equatorial Pacific during the past 50 years (Stramma et al, 2008), conversely with models that simulate increasing O 2 levels with global warming over the historical period (Andrews et al, 2013). A more detailed analysis of the simulated evolution of volumes of low-oxygen waters is given in Sect.…”
Section: General Descriptionmentioning
confidence: 85%
See 1 more Smart Citation
“…Yet there is no such model-data agreement over most of the tropical oceans. Observed time series suggest a vertical expansion of the lowoxygen zones in the eastern tropical Atlantic and the equatorial Pacific during the past 50 years (Stramma et al, 2008), conversely with models that simulate increasing O 2 levels with global warming over the historical period (Andrews et al, 2013). A more detailed analysis of the simulated evolution of volumes of low-oxygen waters is given in Sect.…”
Section: General Descriptionmentioning
confidence: 85%
“…They showed that the model was unable to reproduce the spatial patterns of observed changes. Similarly, Andrews et al (2013) compared output of MPI-ESM-LR and HadGEM2-ES to observations over the historical period. They reported that both models fail to reproduce the pattern of O 2 loss recorded by observations in low-latitude OMZs.…”
Section: Projected Changes In the Extension Of Oxygen Minimum Zonesmentioning
confidence: 99%
“…Oxygen data are the basis for improving estimates of the land carbon sink (Keeling et al, 1996) and, for identifying any emergent fingerprint (Andrews et al, 2013), an extensive O 2 measurement programme is needed. In addition, measurements of at least two carbon variables of the marine inorganic carbon system are necessary.…”
Section: Observational Databasesmentioning
confidence: 99%
“…The ocean has also taken up ∼30% of anthropogenic carbon dioxide (CO 2 ) that has been released into the atmosphere, decreasing ocean pH, and fundamentally changing ocean carbonate chemistry in all ocean regions, particularly in the cooler, high latitude waters (IPCC, 2013). Other chemical and physical changes in the ocean attributed to anthropogenic forcing include declines in dissolved oxygen concentrations (Andrews et al, 2013) and alteration of ocean circulation (Cai et al, 2005;Wu et al, 2012). These anthropogenic changes represent risks to marine life and ecosystems (Poloczanska et al, 2013;Gattuso et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%